Rural community libraries in Africa challenges and impacts - Goodman, Valeda Dent; Goodman, Geoff 1961-; Kevane, Michael (Advances in library and information science (ALIS) book series, 2014)
"This book investigates the relationship between local libraries and community development, from the historical roots of rural libraries to their influence on the literacy, economy, and culture of the surrounding region"..